Outcomes of Cardiac Resynchronization Therapy with Image-Guided Left Ventricular Lead Placement at the Site of Latest Mechanical Activation: A Systematic Review and Meta-Analysis. (20th May 2022) - Allen LaPointe, Nancy M.; Ali-Ahmed, Fatima; Dalgaard, Frederik; Kosinski, Andrzej S.; Schmidler, Gillian Sanders; Al-Khatib, Sana M.
Abstract : Aim . To assess evidence for an image-guided approach for cardiac resynchronization therapy (CRT) that targets left ventricular (LV) lead placement at the segment of latest mechanical activation. Methods . A systematic review of EMBASE and PubMed was performed for randomized controlled trials (RCTs) and prospective observational studies from October 2008 through October 2020 that compared an image-guided CRT approach with a non-image-guided approach for LV lead placement. Meta-analyses were performed to assess the association between the image-guided approach and NYHA class improvement or changes in end-systolic volume (LVESV), end-diastolic volume (LVEDV), and ejection fraction (LVEF). Results . From 5897 citations, 5 RCTs including 818 patients (426 image-guided and 392 non-image-guided) were identified. The mean age ranged from 66 to 71 years, 76% were male, and 53% had ischemic cardiomyopathy. Speckle tracking echocardiography was the primary image-guided method in all studies. LV lead placement within the segment of the latest mechanical activation (concordant) was achieved in the image-guided arm in 45% of the evaluable patients. There was a statistically significant improvement in the NYHA class at 6 months (odds ratio 1.66; 95% confidence interval (CI) [1.02, 2.69]) with the image-guided approach, but no statistically significant change in LVESV (MD −7.1%; 95% CI [−16.0, 1.8]), LVEDV (MD −5.2%; 95% CI [−15.8, 5.4]), or LVEF (MD 0.68; 95% CI [−4.36, 5.73]) versus the non-image-guided approach. Conclusion . The image-guided CRT approach was associated with improvement in the NYHA class but not echocardiographic measures, possibly due to the small sample size and a low rate of concordant LV lead placement despite using the image-guided approach. Therefore, our meta-analysis was not able to identify consistent improvement in CRT outcomes with an image-guided approach.